Attitude and behavior of Indonesian consumers in cross-border online shopping - Kristina Vika Natalia; Ike Janita Dewi (Jurnal Manajemen dan Pemasaran Jasa, 2024)
Abstract   The digital technology enhancement and the COVID-19 pandemic have fastened the growth of cross-border e-commerce. Using the Theory of Planned Behavior as the main framework, we study the effect of belief on the quality of e-website service,  customer need for uniqueness, normative beliefs, subjective norms, self-efficacy, and perceived behavioral control on attitude and behavior intention to shop online across national borders.  This research provides empirical evidence on Indonesian consumers' attitudes and behavior in cross-border online shopping. Based on 200 respondents’ responses, we analyzed the data employing Structural Equation Modeling and Mean-Difference tests.The results of this study reveal that the antecedents of e-website service quality have significant effects on attitudes which in turn affect cross-border online learning behavior intention, but not for consumer need for uniqueness. This study also shows that marketers should pay attention to the demograhic characteristics of consumers which results in differences in predictors and intention in cross-border online shopping. The research extends the Theory of Planned Behavior by adding consumers characteristics in the context of cross-border online shopping. Global e-business companies need to study antecedents in understanding the complexity of Indonesian consumer online shopping behavior across national borders.